2009
DOI: 10.17796/jcpd.33.4.r83r38423x58h38w
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Trioxide Aggregate as Pulp Capping Agent for Primary Teeth Pulpotomy: 2 Year Follow Up Study

Abstract: The aim of the present study was to clinically and radiographically evaluate Mineral Trioxide Aggregate(MTA) as an agent for pulpotomy in primary teeth and to compare it with that of formocresol (FC) pulpotomy. Nineteen children between the ages of 6 to 8 years with 40 carious primary molars were treated with pulpotomy using either FC or MTA. All the molars were evaluated clinically and radiographically at regular intervals over a twenty four month period. The observations were tabulated and statistically anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
15

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 11 publications
2
35
1
15
Order By: Relevance
“…4.7). Formocresol also has also been reported to show a greater amount of root resorption than MTA (Aeinehchi et al 2007;Moretti et al 2008;Subramaniam et al 2009;Ansari et al 2010;Erdem et al 2011). A recent study comparing GMTA to WMTA revealed no statistical differences in the two materials over a study period of 84 months, although there was more bridging with GMTA (Cardosa-Silva et al 2011).…”
Section: Primary Teethmentioning
confidence: 99%
See 1 more Smart Citation
“…4.7). Formocresol also has also been reported to show a greater amount of root resorption than MTA (Aeinehchi et al 2007;Moretti et al 2008;Subramaniam et al 2009;Ansari et al 2010;Erdem et al 2011). A recent study comparing GMTA to WMTA revealed no statistical differences in the two materials over a study period of 84 months, although there was more bridging with GMTA (Cardosa-Silva et al 2011).…”
Section: Primary Teethmentioning
confidence: 99%
“…Comparative studies have shown MTA to be equal to (Aeinehchi et al 2007;Moretti et al 2008;Subramaniam et al 2009;Ansari et al 2010;Erdem et al 2011) or superior to (Salako et al 2003;Agamy et al 2004;Farsi et al 2005;Holan et al 2005;Fuks & Papagiannoulis 2006;Zealand et al 2010) other medicaments and materials used for primary tooth pulpotomies. Most of the reports are comparative in nature, employing clinical signs and symptoms with radiographic interpretation to determine success or failure.…”
Section: Primary Teethmentioning
confidence: 99%
“…The procedure preserves the vitality of the remaining pulp and helps retain the tooth in a desirable state until normal exfoliation occurs. For these purpose, mineral trioxide aggregate (MTA) has been successfully used as an alternative to formocresol [2][3][4][5][6][7][8][9][10][11] and calcium hydroxide 12,13) due to its favorable physical and biological properties. It is composed mainly of Portland cement, with bismuth oxide included as a radiopacifier.…”
Section: Introductionmentioning
confidence: 99%
“…A manutenção da dentição decídua, sem perdas prematuras, preserva a integridade dos arcos e as funções do sistema estomatognático, previne hábitos deletérios e assegura o desenvolvimento do crescimento facial normal (CAICEDO et al, 2006;FUKS, 2008;SUBRAMANIAM et al, 2009;BLANCHARD;HUGAR;DESHPANDE, 2010;COLL, 2010;GODHI;SOOD;SHARMA, 2011;HUTH et al, 2012).…”
Section: Ingaalpunclassified
“…A procura por soluções e materiais ideais para qualquer área de conhecimento dentro da odontologia deve ser direcionada para o conhecimento e indicação de medicamentos biocompatíveis, visando à ocorrência do processo de reparo e proporcionando regeneração natural e biológica da polpa (CHACKO; KURIKOSE, 2006;MORETTI et al, 2008;SAKAI et al, 2009;SUBRAMANIAM et al, 2009;GODHI;SOOD;SHARMA, 2011). O recente progresso no campo científico celular e molecular proporcionou um melhor entendimento sobre as alterações e o comportamento do tecido pulpar durante o processo de reparo tecidual, permitindo avaliar biologicamente as diferentes estratégias de terapia pulpar OLIVEIRA et al, 2013).…”
Section: Materials Capeador Pulparunclassified